Strengthening Effect of Prestressed Near-Surface-Mounted CFRP Tendon on Reinforced Concrete Beam - Woo-Tai Jung; Jong-Sup Park; Jae-Yoon Kang; Hee Beom Park (Advances in Materials Science and Engineering)
Efforts are being made to use FRP (fiber-reinforced polymer) for reinforcements instead of traditional construction materials like steel owing to its remarkable mechanical properties. Among them, this study developed a CFRP tendon to be used as near-surface-mounted reinforcement together with a dedicated prestressing system and investigates experimentally the strengthening effect considering various variables including the amount of reinforcement, the bond performance, and the strength and damage ratio of the concrete. The test results reveal that one line of reinforcement improved the strengthening performance by about 55% and two lines by 96% and that the bonding of the CFRP tendon enhanced the strengthening performance by 15%. Higher strength and damage of the concrete seem to have a poor effect on the overall strengthening performance. However, the use of CFRP tendon with bond performance higher than 11 MPa, filler, and anchorage system appears to promote stable strengthening behavior.